Ethnography and narrative - Hulst, Merlijn van (Policing and society, 2020)
This paper explores the topic of police storytelling from an ethnographic perspective. Ethnographies have always been full of stories, but it took a while for storytelling as such to draw attention to it within the broader study of police culture. Lately, we have seen increased attention for storytelling in policing. Recent studies cover new ground: they comment on story tellability, on police storytelling among recruits, on the differences across settings, and more. Nevertheless, a more systematic treatment of this topic is still lacking. This paper reviews the literature on police storytelling. Its purpose is to come to a more thorough and critical understanding of storytelling in policing (studies), which allows us to identify some challenges and opportunities we see for future (ethnographic) research.